Spectrophotometer Determination of Cefixime in pure form and pharmaceutical preparation by Using Cloud point Extraction (Baghdad Science Journal, 2020)
Two simple methods spectrophotometric were suggested for the determination of Cefixime (CFX) in pure form and pharmaceutical preparation. The first method is based without cloud point (CPE) on diazotization of the Cefixime drug by sodium nitrite at 5Cº followed by coupling with ortho nitro phenol in basic medium to form orange colour. The product was stabilized and measured 400 nm. Beer’s law was obeyed in the concentration range of (10-160) μg∙mL-1 Sandell’s sensitivity was 0.0888μg∙cm-1, the detection limit was 0.07896μg∙mL-1, and the limit of Quantitation was 0.085389μg∙mL-1.The second method was cloud point extraction (CPE) with using Trtion X-114 as surfactant. Beer’s law was obeyed in the concentration range of (10-160) μg∙mL-1. Sandell’s sensitivity was 0.1470μg∙cm-1, the detection limit was 0.06680μg∙mL-1, and the limit of quantitation was 0.07293μg∙mL-1. All variables including the reagent concentration, reaction time, colour stability period, and mole ratio were studied in order to optimize the reaction conditions. The composition of product (1:1). The methods were effectively useful to the determination of Cefixime in pharmaceutical dose form, and the attained results were in good agreement with the official result and other methods in literature .No interference was observed from the commonly encountered additives and excipients